1992
DOI: 10.1017/s0332586500002560
|View full text |Cite
|
Sign up to set email alerts
|

Clausal Structure and a Tier for Grammatical Marking in American Sign Language

Abstract: Grammatical information in ASL can systematically be marked on the face. Such nonmanual marking extends over the c-command domain of the trigger, and therefore provides information about the hierarchical organization of the language. Consistent with evidence available from the distribution of non-manual markings—as illustrated with respect to wh-marking and negation—a basic clausal structure for ASL is proposed. Furthermore, we suggest, contrary to generally accepted claims about ASL, that both Tense and Agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(22 citation statements)
references
References 9 publications
2
20
0
Order By: Relevance
“…These examples also help to demonstrate a fundamental difference between 'br' and other nonmanual markers. Negation and wh-question marking are argued by Aarons et al (1992aAarons et al ( , 1992b to spread over their c-command domain. Under any proposed analysis, the 'br'-marked phrases in (47)-(51) c-command the rest of the sentence, yet 'br' does not spread over the entire sentence, even when there is no other nonmanual to prevent it from doing so (e.g.…”
Section: 235mentioning
confidence: 95%
See 2 more Smart Citations
“…These examples also help to demonstrate a fundamental difference between 'br' and other nonmanual markers. Negation and wh-question marking are argued by Aarons et al (1992aAarons et al ( , 1992b to spread over their c-command domain. Under any proposed analysis, the 'br'-marked phrases in (47)-(51) c-command the rest of the sentence, yet 'br' does not spread over the entire sentence, even when there is no other nonmanual to prevent it from doing so (e.g.…”
Section: 235mentioning
confidence: 95%
“…The operator feature in wh-questions is [+wh]. In ASL, this feature is associated with brow lowering, what we call brow furrow 'bf,' and spreads over its c-command domain (Aarons et al 1992a(Aarons et al , 1992bMacLaughlin 1997). We will not be further concerned with [+wh] operators; instead, all of the operators that we will deal with are [−wh].…”
Section: Wh-questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…His proposal for grammaticization spans the continuum from lexical item (Verb) to grammatical items (AUX), and eventually to phonologically reduced morphological marker (tense affix). We know that ASL has morphological affixes in the form of aspectual markings discussed by Klima, Bellugi et al (1979), and possibly non-manual tense marking (Aarons et al 1992(Aarons et al , 1995. It remains an open question then whether ASL will take the next step and create a morphological marking for tense derived from a form of FINISH.…”
mentioning
confidence: 99%
“…FINISH as a free-standing sign is not a tense marker in that regard; instead it is an aspect marker of perfective and completion but not of 'past tense. ' Aarons et al (1992' Aarons et al ( , 1995 argue that ASL does have tense indicated by non-manual marking over the verb. However, the presence or absence of such marking over a verb has no bearing on the status of FINISH. To the extent that FINISH indicates perfective aspect, it is also unlike other means of expressing aspect in ASL.…”
mentioning
confidence: 99%